Relationships between language learning strategies, positive emotions, language learning motivation and English language proficiency among Malaysian ESL undergraduates - Mohammadipour, Mohammad (2017)
During the previous decades, a considerable amount of literature was published on the relationship between language learning strategy use and language proficiency. These studies were conducted under the presupposition that more frequent use of language learning strategies is associated with higher language proficiency. However, to date, various studies have revealed contradictory findings. Similarly, second language learning studies have suggested that the construct of emotions is related to second language learning variables, such as language learning strategy use and language learning motivation. As a pioneering research in this realm, this study argues that students’ positive emotions is a mediating variable in the relationships between language learning proficiency, language learning strategy use, and language learning motivation. In this respect, this study was aimed at investigating the use of English learning strategies among Malaysian ESL undergraduates. In addition, it attempted to determine whether there is any significant difference in the use of language learning strategies across English proficiency levels among the participants. It also aimed to compare the frequent users and under-users of language learning strategies in terms of their levels of positive emotions. Finally, it examined the relationships between language learning strategy use, positive emotions, and language learning motivation. The theoretical bases of the study were the broaden and build theory (Fredrickson, 2001), Pekrun’s (2006) control-value theory of academic emotions, and Gardner’s motivation theory (1985). This study adopted a sequential mixed methods design. In total, 750 Malaysian ESL undergraduates were selected through stratified random sampling from five Malaysian public universities. The quantitative data were collected through three sets of questionnaires: (a) Oxford's (1990) Strategy Inventory for Language Learning (SILL), Fredrickson's (2009) modified Differential Emotional Scale (mDES), and Perez's (2013) Attitude and Motivational Test Battery (AMTB). Moreover, the follow up qualitative data were gathered through semi-structured interviews and focus group discussion with a select number of the participants. For the quantitative data, a series of MANOVAs, ANOVAs, t-tests and correlational analyses were employed, whilst for the qualitative data, the value-laden responses were transcribed, coded thematically, and analysed. The findings of the study indicate that Malaysian ESL undergraduates have a medium degree of strategy use and there are significant differences in their overall uses of language learning strategies across proficiency levels. Furthermore, the findings revealed significant discrepencies in positive emotions levels across users of language learning strategies. A positive significant relationship was also found between positive emotions, overall language learning strategy use, and different categories of language learning strategies. The qualitative findings demonstrated that there is consistencey between learners’ enhanced experience of positive emotions and their tendency to apply a greater variety of language learning strategies. The findings of the study underscore the importance of students’ positive emotions in their language learning strategy use and language learning motivation, which in turn, are related to their language proficiency. The study proposes further consideration of positive and negative emotions in future studies on language learning as they seem to have significant bearing on English language learning.